2000
DOI: 10.1002/1097-0142(20000715)89:2<412::aid-cncr29>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Loss of tissue transglutaminase as a biomarker for prostate adenocarcinoma

Abstract: BACKGROUND Additional molecular tissue biomarkers for prostate carcinoma are needed to stratify patients with clinically suspicious findings, such as an elevated prostate specific antigen (PSA) with a negative biopsy, according to risk. METHODS Prostate tissues from 43 cancer cases and 47 controls with no evidence of cancer were labeled for transglutaminase by immunohistochemistry. Immunoreactivity was quantified using the Autocyte Pathology Workstation. In addition, quantitative fluorescence image analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Conversely, RA-mediated TGase expression was suppressed in fibroblasts expressing an oncogenic form of Ras (16,17), implying that retinoid-stimulated TGase expression was inconsistent with the Ras-transformed phenotype. As a result of these and similar findings, such as the proposed use of TGase hypoexpression as a biomarker for prostate cancer (18), it has become generally accepted that TGase promotes cellular processes that limit cell number. However, recent evidence suggests that TGase may not be detrimental to the growth of all cell types.…”
mentioning
confidence: 77%
“…Conversely, RA-mediated TGase expression was suppressed in fibroblasts expressing an oncogenic form of Ras (16,17), implying that retinoid-stimulated TGase expression was inconsistent with the Ras-transformed phenotype. As a result of these and similar findings, such as the proposed use of TGase hypoexpression as a biomarker for prostate cancer (18), it has become generally accepted that TGase promotes cellular processes that limit cell number. However, recent evidence suggests that TGase may not be detrimental to the growth of all cell types.…”
mentioning
confidence: 77%
“…With immunohistochemistry staining and immunofluorescence assays, Birckbichler et al (30) showed that expression and activity of TGM4 in prostate adenocarcinoma was significantly lower than normal prostate, benign prostatic hyperplasia, and inflammation tissues. The tumor suppressor PTEN induces TGM4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Upon secretion, TG2 is activated by the high level of Ca 2ϩ in the extracellular space and functions as a cross-linking enzyme in the matrix (28). There are numerous reports of downregulation of TG2 in aggressive tumors and metastases (30)(31)(32)(33). Recombinant TG2 applied to rat mammary adenocarcinomas implanted in dorsal skin window chambers produced significant growth delay in the tumors (34), and transfection of TG2 into a highly malignant hamster fibrosarcoma cell line led to significant reduction of tumor incidence (35).…”
Section: Gpr56 Is a Gpcr Implicated In Multiple Biologicalmentioning
confidence: 99%